The Next Generation of Social Products Based on Sensing, Smart and Sustainable (S3) Features: A Smart Thermostat as Case Study. Issue 13 (2019) - Ponce, Pedro; Meier, Alan; Miranda, Jhonattan; Molina, Arturo; Peffer, Therese
Abstract: Since Internet of Things (IoT), Machine Learning, Digital Systems, Control Systems were incorporated in product design, a new designing technology era raised up so the conventional methods for developing products could not be valid anymore since they do not include social features that allow interacting with consumers and other products. Sometimes, the products are extremely limited in the social communication between products to consumers and products to products, and the primary communication system is the interface, but typically, this interface is not designed as a social element. As a result, social communication is minimal. Thus, a basic design methodology that allows product designers to incorporate social factors between products to consumers and products to products is presented in this paper. Also, the term social communication PCPP (Product-Consumer and Product-Product) is coined as a part of the product design methodology that allows defining the social features as primary elements in the process of designing products. Besides, a conceptual method for smart thermostats is proposed for a social communication PCPP to demonstrate how this conceptual proposal could be implemented using the sensing, smart and sustainable (S 3 ) features.